Strategies to Improve Character Building for the Young Generation to Minimize Juvenile Delinquency at SMK Mandalahayu 2 Bekasi - Rr Dinar Soelistyowati; Salsabila Dinda Heriyani; Adinda Trianurahmah; Kadek Ayu Oktavia (Indonesian Journal of Society Development, 2023)
The purpose of organizing this service activity has the goal of increasing the knowledge of SMK Mandalahayu 2 Bekasi students on understanding Character Building. Juvenile delinquency is inseparable from the lack of parenting, so at school students must learn what is meant by Character Building in order to adapt and adjust their respective roles in society. The activity was carried out through the counseling method in the classroom where the implementation of the activity was carried out on January 10, 2023. The results of this activity are hoped that the students of SMK Mandalahayu 2 will not be easily provoked by negative activities that have an impact on social problems and damage in their environment. So that juvenile delinquency can be minimized